Successful Laparoscopic Cholecystectomy of Giant Gallstone – A Case Report Study - Saman Taher Barzinjy (Diyala Journal of Medicine)
Background: Gallstone diseases are the most common biliary pathologies. They are very frequent in the Western world, where the approximate incidence is about 10–15%. Laparoscopic cholecystectomy is the method of choice for treating gallstone disease. The conversion rate of laparoscopic to open surgical procedures is estimated to be about 4%- 5%. Gallstone size is important since large/giant gallstones are more liable for technical difficulties during laparoscopic interventions.